1998
DOI: 10.1164/ajrccm.157.1.9706079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on Sleep Apnea in Men

Abstract: The effects of age on the prevalence of sleep apnea in the general population remain unclear, because previous studies have focused on specific populations. The effects of age on the severity of apnea are unknown. This study was based on a two-stage general random sample of men (aged 20 to 100 yr), consisting of a telephone survey (n = 4,364) and a sleep laboratory evaluation of a survey subsample (n = 741). Obstructive sleep apnea (OSA), based on both sleep laboratory and clinical criteria (apnea/hypopnea ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
697
15
63

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,104 publications
(833 citation statements)
references
References 27 publications
58
697
15
63
Order By: Relevance
“…Young 29 has previously suggested an heuristic model with sleep apnoea as both an age related disorder seen at lower ages and an age dependent condition in the elderly, with a potential overlap in the 60-70 year age range. This hypothesis was supported by the results of a population based study of the prevalence and severity of OSAS in men aged 20-100 years by Bixler et al 30 who found that the prevalence of sleep apnoea tended to increase with age. On the other hand, the maximum prevalence of OSAS, defined as an AHI of >10 and the presence of daytime symptoms, was in the middle age group (45-64 years).…”
Section: Discussionmentioning
confidence: 70%
“…Young 29 has previously suggested an heuristic model with sleep apnoea as both an age related disorder seen at lower ages and an age dependent condition in the elderly, with a potential overlap in the 60-70 year age range. This hypothesis was supported by the results of a population based study of the prevalence and severity of OSAS in men aged 20-100 years by Bixler et al 30 who found that the prevalence of sleep apnoea tended to increase with age. On the other hand, the maximum prevalence of OSAS, defined as an AHI of >10 and the presence of daytime symptoms, was in the middle age group (45-64 years).…”
Section: Discussionmentioning
confidence: 70%
“…Secondly, despite a wide spectrum of SDB being present in the current population, mild cases were prevalent, the absence of severe cases may reduce the relationship between CRP and AHI. However, this finding is common in clinical and epidemiological studies; severe cases are more common in young patients [48]. Thirdly, the examined elderly subjects were noninstitutionalised and therefore they might constitute a survivor group more resistant to vascular risk and stress.…”
Section: Discussionmentioning
confidence: 93%
“…De acordo com pesquisas já realizadas, o ronco tende a aumentar com a idade (6,11). Estudos direcionados à prevalência foram realizados em uma população de homens e mulheres com idade entre 20 e 100 anos, os quais foram separados em subgrupos e apresentaram como resultado a maior prevalência de ronco em mulheres acima de 65 anos e nos homens entre 45 e 64 anos (26,27). …”
Section: Gráfico 1 -Gênero E Pontuação Média Na Escala De Epworthunclassified